1999
DOI: 10.1161/01.cir.100.11.1182
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Vascular Remodeling After Balloon Angioplasty and β-Radiation Therapy

Abstract: A different pattern of remodeling is observed in coronary segments treated with beta-radiation after successful balloon angioplasty. In the irradiated segments, the adaptive increase of EEM volume appears to be the major contributor to the luminal volume at follow-up. Conversely, both edges showed an increase in plaque volume without a net change in EEM volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(72 citation statements)
references
References 36 publications
6
60
1
5
Order By: Relevance
“…The rationale for the use of radiation therapy for the prevention and treatment of vascular stenosis as a result of neointimal hyperplasia stems from (1) the potent in vitro antiproliferative effect of radiation therapy on smooth muscle cells, endothelial cells, and macrophages (72)(73)(74) and (2) possible beneficial effects on vascular remodeling (vessel wall dilation) (75). Experimental angioplasty models have demonstrated significant reductions in luminal stenosis with endovascular and external beam radiation therapy (76,77), and these findings have been confirmed in large clinical studies of catheter-based radiation therapy for coronary restenosis (78,79).…”
Section: Radiation Therapymentioning
confidence: 99%
“…The rationale for the use of radiation therapy for the prevention and treatment of vascular stenosis as a result of neointimal hyperplasia stems from (1) the potent in vitro antiproliferative effect of radiation therapy on smooth muscle cells, endothelial cells, and macrophages (72)(73)(74) and (2) possible beneficial effects on vascular remodeling (vessel wall dilation) (75). Experimental angioplasty models have demonstrated significant reductions in luminal stenosis with endovascular and external beam radiation therapy (76,77), and these findings have been confirmed in large clinical studies of catheter-based radiation therapy for coronary restenosis (78,79).…”
Section: Radiation Therapymentioning
confidence: 99%
“…5,9 In brief, the segment subject to 3-D reconstruction was examined with a 30-MHz singleelement mechanical transducer IVUS system (ClearView, CVIS; Boston Scientific Corp). ECG-gated 3-D IVUS image acquisition and digitization were performed with a computerized workstation (EchoScan; TomTec).…”
Section: Ivus Image Acquisition Analysis Systemmentioning
confidence: 99%
“…5 An angiogram was performed during contrast injection after positioning of the delivery catheter, and the relation between anatomic landmarks and the 2 radiopaque markers of the radiation source was noted. Typically, the aorto-ostial junction, side branches, stent, or a combination were used as landmarks.…”
Section: Ivus Image Acquisition Analysis Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rapid decrease in the dose of beta radiation within 2-5mm of depth is associated with a less homogeneous release of the dose 32 . In addition, the "shield effect" produced by the rods of the stent could be associated with an attenuation in the radiation dose through its rods greater than 15% 36 . Comparing the results on intracoronary ultrasound in 2 large studies 13,15 , beta radiation showed a greater benefit than gamma radiation did in preventing neointimal hyperplasia inside the stent 37,38 .…”
Section: Discussionmentioning
confidence: 99%